Perceções sobre as abordagens à aprendizagem - estudo de variáveis psicológicas - Lourenço, Abílio Afonso; Nogueira, Carla Maria Leite (Educação e Filosofia, 2014)
*Doutor em Psicologia da Educação pela Universidade do Minho, Braga, Portugal. ProfessorÂ titular do Agrupamento de Escolas Alexandre Herculano, Porto, Portugal. Investigador da Universidade do Minho e do Centro de Investigação em Psicologia e Educação doÂ Agrupamento de Escolas Alexandre Herculano.**Licenciada em Matemática pela Faculdade de Ciências da Universidade do Porto.Â Professora de Matemática no Agrupamento de Escolas de S. João de Sobrado, Valongo,Â Portugal.Perceções sobre as abordagens à aprendizagem - estudo de variáveis psicológicasResumo:Â Esta investigação, realizada numa escola básica no norte de Portugal, tem como objetivo analisar as perceções que os alunos apresentam sobre algumas variáveis relativas à forma como desenvolvem a sua aprendizagem, nomeadamente: a autorregulação para a aprendizagem; os processos de estudo utilizados; o controlo volitivo; a planificação da gestão do tempo; e a procrastinação. Outra finalidade deste estudo éverificar se existe uma relação significativa entre estas variáveis e a perceção de autoeficácia revelada pelos alunos, assim como com os níveis exibidos no final do 1º período, nas disciplinas de Língua Portuguesa, Inglês, Matemática e Ciências Naturais. São apresentadas, também, algumas implicaçõespara a prática educativa.Palavras-chave: Abordagens à aprendizagem. Percepções de autoeficácia. Ensino básico.Perceções sobre as abordagens à aprendizagem - estudo de variáveis psicológicasAbstract: This research, conducted in a basic school in northern Portugal, aims to analyze the perceptions that students have about some variables regarding how to develop their learning, namely: self-regulation for learning; study the processes used, the control volitional; planning time management, and procrastination. Another purpose of this study is to determine whether there is a significant relationship between these variables and the perception of self-efficacy revealed by the students, as well as the levels shown at the end of the 1st period, in the discipline of Portuguese, English, Mathematics and Natural Sciences. We present also some implications for educational practice.Keywords: Approaches to learning. Perceptions of self-efficacy. Basic education.Data de registro: 07/02/2013Data de aceite: 20/11/2013Referências:ABLARD, K.; LIPSCHULTZ, D. Self-regulation in high-achieving students: relations to advanced reasoning, achievement goals, and gender. Journal of Educational Psychology, 90 (1), p. 94-101, 1998.AMES, C. A. Motivation: what teachers need to know. Teachers College Record, 91 (3), p. 409-421, 1990.ANDERMAN, E. M. & MAEHR, M. L. Motivation and schooling in the middle grades. Review of Educational Research, 64 (2), p. 287-309, 1994.BANDURA, A. Social foundations of thought and action: A social cognitive theory. Englewood Cliffs, NJ: Prentice-Hall, 1986.BARCA, A.; PORTO, A.; SANTORUM, R. Los enfoques de aprendizajeen contextos y situaciones educativas. Una aproximación conceptual e metodológica. In: BARCA, A.; MALMIERCA, J. L.; NÚÃ‘ EZ, J. C.; PORTO, A.; SANTORUM, R. (Ed.). Procesos de aprendizaje en ambientes educativos. Madrid: Editorial Centro de Estudios Ramón Areces, 1997. p. 387-435.BIGG S, J. B. Approaches to learning in secondary and tertiary students in Hong Kong: some comparative studies. Educational Research Journal, 6, p. 27-39, 1991.BIGG S, J. B. What do inventories of students' learning processes really measure? Atheoretical review and clarification. British Journal of Educational Psychology, 63 (1), p. 3-19, 1993.__________. Teaching for quality learning at university. 2. ed. Buckingham: Open University Press/Society for research into Higher Education, 2003.__________; MOORE, P. J. The process of learning. Sydney: Prentice Hall of Australia, 1993.BOEKAERTS, M. Personality and the Psychology of Learning. European Journal of Personality, 10, 377-404, 1996.__________. Self-regulation. With a focus on the self-regulation of motivation and effort. In: RAMON, W.; LERNER R. (Series Ed.); SIGEL, I. E.; RENNINGER, K. A. (Vol. Ed.). Handbook of Child Psychology: Child psychology in practice. v. 4. 6. ed. NY: Wiley, 2005. p. 115-126.__________; CORNO, L. Self-Regulation in Classroom: A Perspective on Assessment and Intervention. Applied Psychology: An International Review, 54 (2), p. 199-231, 2005.BORUCHOVITCH, E. A motivação para aprender de estudantes em cursos de formação de professores. Educação, 31 (1), p. 30-38, 2008.BYR NE, B. M. Structural Equation Modeling With AMOS - Basic Concepts, Applications, and Programming. NJ: Lawrence Erlbaum, 2001.BZUNECK, A. Uma abordagem sócio-cognitivista à motivação do aluno: A teoria de metas de realização. Psico-USF, 4 (2), p. 51-66, 1999.CORNO, L. The best-laid plans. Modern conceptions of volition and educational research. Educational Research, 22, p. 14-22, 1993.__________. Work habits and work styles: Volition in education. Teachers College Record, 106, p. 1669-1694, 2004.__________; KANFER, R. The role of volition in learning and performance. In: DARLING-HAMMOND, L. Review of Research in Education. v. 19.Washington, DC: American Educational Research Association, 1993. p. 301-341.DE VOLDER, M. L.; LENS, W. Academic achievement and future time perspective as a cognitive-motivational concept. Journal of Personality and Social Psychology, 42 (3), p. 566-571, 1982.DECI, E. L. The "What" and "Why" of Goal Pursuits: Human Needs and the Self-Determination of Behavior. Psychological Inquiry, 11(4), p. 227- 268, 2000.__________. RY AN, R. M. Intrinsic motivation and self-determination in human behavior. NY: Plenum Press, 1985.DEWITTE, S.; LENS, W. Procrastinators lack a broad action perspective. European Journal of Personality, 14, p. 121-140, 2000.ELLIOTT, E.; DWECK, C. S. Goals: An approach to motivation and achievement. Journal of Personality and Social Psychology, 54 (1), p. 5-12, 1988.ENTWISTLE, N. J. Motivational factors in students' approaches to learning. In: SCHMECK, R. R. (Ed.). Learning Strategies and Learning Styles. NY: Plenum Press, 1988. p. 1-51.__________. Frameworks for Understanding as Experienced in Essay Writing and in Preparing for Examinations. Educational Psychologist, 30 (1), p. 47-54, 1995.FEARN-WANNAN, H.(1980). Students' of lecturers as determinants of academic performance in first-year chemistry. In: BILLING, D. (Ed.). Course design and student learning. Guildonf: SRHE, 1980. p. 76-89.FERR ARI, J.; HARR IOTT, J.; EVANS, L.; LECIK-MICHNA, D.; WENGER, J. Exploring the time preferences by procrastinators: Night or day, which is the one? European Journal of Personality, 11 (3), p. 187-196, 1997.__________; JOHNSON, J.; MCCOWN, W. Procrastination and task avoidance: Theory, research and practice. NY: Plenum Press, 1995.__________; O'CALLAGHAN, J.; NEWBEGIN, I. Prevalence of procrastination in the United States, United Kingdom, and Australia: arousal and avoidance delays among adults. North American Journal of Psychology, 7 (1), p. 1-6, 2005.FIGUEIRA, A. P. C. Em torno do rendimento escolar. 1994. Tese (Mestrado) - Faculdade de Psicologia e Ciências da Educação da Universidade de Coimbra, Coimbra, 1994.GAINE, C.; GEORG E, R. Gender, "race", and class in schooling. London: Falmer Press, 1999.GIBBS, G. Improving the Quality of Student Learning. Bristol: Technical and Educational Services, 1992.HARR IS, N.; SUTTON, R. Task procrastination in organizations: A framework for research. Human Relations, 36 (11), p. 987-995, 1983.KARABENICK, S. A. Help seeking as a strategic resource. In: KARABENICK, S. A. (Ed.). Strategic help seeking: Implications for learning and teaching. Mahwah, NJ: Erlbaum, 1998. p. 1-11.KUHL, J. Volitional mediators of cognitive behavior consistency: Selfregulatory processes and action versus state orientation. In: __________.; BECKMAN, J. (Ed.). Action control. NY: Springer, 1985. p. 101-128.LENS, W. La signification motivationnelle de la perspective future. Revue Québécoise de Psychologie, 14 (1), p. 69-83, 1993.LOPES DA SILVA, A. ; SÃ, I. Auto-Regulação e Aprendizagem. Investigar em Educação. Revista da Sociedade Portuguesa de Ciências da Educação, 2, p. 71-90, 2003.LOURENÇO, A. A. Multiculturalidade, etnia e personalidade. Revista de Psiquiatria e Psicologia, 25, 1-2-3-4, p. 29-50, 2004.__________. Processos Auto-Regulatórios em Alunos do 3º Ciclo do Ensino Básico: Contributos da Auto-Eficácia a da Instrumentalidade. 2008.Dissertação (Doutorado em Educação). Instituto de Educação e Psicologia da Universidade do Minho, Braga, 2008. Não publicada.__________; PAIVA, M. O. A. Conflitos na escola: a importância da amabilidade na negociação. Educação e Filosofia, 23 (46), p. 145-168, 2009.__________; DA ROSA, V. M. P.; PAIVA, M. O. A. Ambiente psicossociológico da sala de aula e rendimento escolar: um estudo de caso. Revista da Faculdade de Ciências Humanas e Sociais, 7, p. 276-289, 2010.__________; PAIVA, M. O. A. A motivação escolar e o processo de aprendizagem. Ciências & Cognição, 15 (2), p. 132-141, 2010a.__________; PAIVA, M. O. A. A percepção do clima de escola pelos alunos da ESAH. In: Semin ário Inte rnacional Cont ributos da Psicolo gia em Contextos Educativos , 1., 2010, Braga. Actas... Braga: Edição Universitária, 2010b. (Apresentação de trabalho).__________; ROSÃR IO, P.; SALGADO, A.; GUIMARÃ ES, C.; TRIGO, L.; BALDAQUE, M.; COSTA, M.; PAIVA, M. O. A; SANTOS, L.; MOURÃ O, R.; MAGALHÃES, C.; VALLE, A.; NÚÃ‘ EZ, J. C. & GONZÃ LEZ-PIENDA, J. Processos auto-regulatórios em alunos do 3º Ciclo do Ensino Básico: Auto-eficácia e instrumentalidade. In: Con gresso Inte rnacional de Avalia ção Psicol ógica : fo rmas e contextos , 13., 2008, Braga: Edição Universitária. (Apresentação de trabalho).__________; PAIVA, M. O. A.; YOUNG, N.; DA ROSA, V. P. Effects of personality on interpersonal negotiation strategies and self-presentation in a school setting. Psique, 6 (1), p. 7-27, 2010.LOWE, B.; WARD, S.; WINZAR, H. (2007). Essentials of SPSS for Windows Versions 14 and 15. Australia: Cengage Learning, 2007.MAIA, J. A. R.; GR AÇA, A. Validade de construto e invariância configuracional de instrumentos psicológicos. Uma abordagem psicológica a partir da teoria psicométrica e do LISREL. In: Con gresso de Educa ção Física e Ciências do Despo rto dos Países de Língua Portu guesa , 5., 1995, Coimbra. Anais... Coimbra. (Apresentação de comunicação).MARTON, F. What does it take to learn? In: ENTWISTLE, N. J. (Ed.). Strategies for researchand development in higher education. Amsterdam: Swets and Zeitlinger, 1975. p. 32-43.__________. Describing and Improving Learning. In: SCHMECK, R. (Ed.). Learning strategies and learning styles. NY: Plenum Press, 1988. p. 53-82.MARTON, F.; BOOTH, S. Learning and awareness. NJ: Lawrence Erlbaum, 1997.__________; CARLSSON, M. A.; HALÃSZ, L. Differences in understanding and the use of reflective variation in reading. British Journal of Educational Psychology, 62, p. 1-16, 1992.__________; HOUNSELL, D.; ENTWISTLE, N. (Ed.). The Experience of Learning. Edinburgh: Scottish Academic Press Limited, 1997.__________; SÃ„LJÃ–, R. On qualitative differences in learning: I - Outcome and Process. British Journal of Educational Psychology, 46, p. 4-11, 1976a.__________; SÃ„LJÃ–, R. On qualitative differences in learning: II. Outcome as a function of the learner's conception of the task. British Journal of Educational Psychology, 46, p. 115-127, 1976b.__________; SÃ„LJÃ–, R. Approaches to learning. In: MARTON, F.; HOUNSELL, D.; ENTWISTLE, N. (Ed.). The Experience of Learning. Edinburgh: Scottish Academic Press Limited, 1997. p. 39-58.__________; WATKINS, D.; TANG, C. Discontinuities and continuities in the experience of learning: An interview study of high-school students in Hong-Kong. Learning and Instruction, 7 (1), p. 21-48, 1997.__________; WEN, Q.; NAGLE, A. Views on learning in different cultures. Comparing patterns in China and Uruguay. Anales de Psicologia, 12 (2), p. 123-132, 1996.MONTERO, C. R.; TORR ES, M. G. Capacidad de autorregulación del proceso de aprendizaje. In: Gon zále z-Pienda , J. A.; Pérez Núnez (Coord.). Dificultades del aprendizaje escolar. Madrid: Psicología Pirámide, 1998. p. 239-259.MONTGOMERY , D. Enhancing student learning in higher education through the development and use of cognitive process strategies. In: Gibbs , G. (Ed.). Improving student learning-theory and practice. Oxford: The Oxford Centre of Staff Development, 1994. p. 36-49.NEWMAN, R. S. Academic help-seeking: A strategy of self-regulated learning. In: Schun k, D. H.; Zimme rman , B. J. (Ed.). Self-regulation of learning and performance: Issues and educational applications. Hillsdale: Erlbaum, 1994. p. 283-301.NICHOLLS, J. Achievement motivation: Conceptions of ability, subjective experience, task choice, and performance. Psychological Review, 91, p. 328-346, 1984.NÚÃ‘ EZ, J. C.; SOLANO, P.; GONZÃ LEZ-PIENDA, J. A.; ROSÃR IO, P. El aprendizaje autoregulado como medio y meta de la educación. Papeles del Psicólogo, 27 (3), p. 141-148, 2006.NUTTIN, J. C. Théorie de la motivation humaine. Paris: Presses Universitaires de France, 1985.__________; LENS, W. Future time perspective and motivation: Theory and research method. Louvain: Presses Universitaires de Louvain, 1985.PAIVA, M. O. A. Abordagens à aprendizagem e abordagens ao ensino: Uma aproximação à dinâmica do aprender no Secundário. 2008.Dissertação (Doutorado em Educação). Instituto de Educação e Psicologia da Universidade do Minho, Braga, 2008. Não publicada.__________; LOURENÇO, A. A. Inventário de Percepções de Ambiente de Ensino (IPAE): Validação numa perspectiva exploratória. Psicologia, Educação e Cultura, 15 (1), p. 23-35, 2011a.__________; LOURENÇO, A. A. Ambiente da sala de aula: um estudo de caso. Educação e Filosofia, 25 (49), p. 17-42, 2011b.__________; LOURENÇO, A. A. Rendimento Académico: Influência do Autoconceito e do Ambiente de Sala de Aula. Psicologia: Teoria e Pesquisa, 27 (4), p. 393-402, 2011c.PEREZ, J. N.; GONZALEZ-PIENDA, J. A.; RODRIGUEZ, M. Aprender en la escuela. In: Gon zále z-Pienda , J. A.; Pérez Núnez (Coord.). Dificultades del aprendizaje escolar. Madrid: Psicología Pirámide, 1998. p. 21-43.PINTRICH, P. R. The role of goal orientation in self-regulated learning. In: Boe kae rts , M.; Pint rich , P.; Zeidne r, M. (Ed.). Handbook of self-regulation. San Diego: Academic Press, 2000. p. 451-502.__________. A motivational science perspective on the role of student motivation in learning and teaching contexts. Journal of Educational Psychology, 95, p. 667-686, 2003.__________; ZUSCHO, A. The development of academic self-regulation: the role of cognitive and motivational factores. In: Wigfield , A.; Eccles , J. (Ed.). Development of achievement motivation. NY: Academic Press, 2002. p. 250-271.PROSSER, M.; TRIGWELL, K. Understanding Learning and Teaching: The Experience in Higher Education. Buckingham: Open University Press, 2000.RAMSDEN, P. Learning to Teach in Higher Education. London: Routledge, 1992.REEVE, J.; DECI, E. L.; RY AN, R. M. Self-determination theory: a dialectical framework for understanding sociocultural influences on student motivation. In: MC Ine rne y, Dennis; Van Etten , Shawn (Ed.). Big theories revisited. Greenwich: Information Age Publishing, 2004. p. 31-60.RICHARDSON, J. T. E. Meaning orientation and reproducing orientation: A typology of approaches to studying in higher education? Educational Psychology, 17 (3), p. 301-311, 1997.ROSÃR IO, P. Variáveis Cognitivo-motivacionais na Aprendizagem: As "Abordagens ao Estudo" em alunos do Ensino Secundário. 1999. Tese (Doutorado em Psicologia) - Universidade do Minho, Braga, 1999.__________; COSTA, M. A procrastinação, auto-regulação e género. 2007. Dissertação (Mestrado)-Universidade do Minho, Braga, 2007.ROSÁRIO , P.; GRÃCIO , L.; NÚNE Z, J. C.; GON ZÃLE Z-PIENDA , J. Voix d'élèves sur l'apprentissage à l'entrée et à la sortie de l'université: um regard phénoménographique. Revue des Sciences de l'éducation, 33 (1), p. 237-262, 2007.__________; LOURENÇO, A. A.; PAIVA, M. O.; NÚÃ‘ EZ, J. C.; GONZÃ LEZ-PIENDA, J.; VALLE, A. Inventário de processos de autoregulação da aprendizagem (IPAA). In: Machado , C.; Gon çalves , M. M.; Almeid a, L. S.; Sim ões , M. R. (Coord.). Instrumentos e Contextos da Avaliação Psicológica. v. I. Coimbra: Almedina, 2011. p. 159-174.__________; FERR EIRA, I.; CUNHA, A. Inventário de Processos de Estudo (IPE). In: Gon çalves , M.; Sim ões ,M.; Almeida , L.; Machado , C. (Coord.). Avaliação psicológica: instrumentos validados para a população portuguesa. v. 1. Coimbra: Quarteto Editora, 2003.__________; FERR EIRA, I.; GUIMARÃ ES, C. Abordagens ao estudo em alunos de alto rendimento. Sobredotação, 2 (2), p. 121-137, 2001.__________; MOURÃ O, R.; SALGADO, A.; RODRIGUES, A.; SILVA, C.; MARQ UES, C.; AMORIM, L.; MACHADO, S.; NÚÃ‘ EZ, J.; GONZÃ LEZ-PIENDA, J.; HERNÃNDEZ-PINA, F. Trabalhar e estudar sob a lente dos processos e estratégias de auto-regulação da aprendizagem. Psicologia, Educação e Cultura, 10 (1), p. 77-88, 2006.__________; NÚÃ‘ EZ, J. C.; GONZÃ LEZ-PIENDA, J. Sarilhos do Amarelo. Porto: Porto Editora, 2007.__________. NÚÃ‘ EZ, J. C.; GONZÃ LEZ-PIENDA, J. A.; ALMEIDA, L.; SOARES, S.; RÚ BIO, M. El aprendizaje escolar examinado desde la perspectiva del "Modelo 3P" de J. Biggs. Psicothema, 17 (1), p. 20-30, 2005.__________; SOARES, S.; NÚÃ‘ EZ, J. C.; GONZÃ LEZ-PIENDA, J.; RÚ BIO, M. Auto-regulação da aprendizagem em contexto escolar: questões e discussões. In: Encont ro do Grupo de trabalho - Peda gogia pa ra a Autonomia (GT-PA), 2., 2003, Braga, Portugal. Actasâ€¦ Braga, Portugal: Universidade do Minho, 2003.RY AN, R. M.; DECI, E. L. Self-determination theory and facilitation of intrinsic motivation, social development and well-being. American Psychologist, 55 (1), p. 68-78, 2000.__________; PINTRICH, P. R. Should I ask for help? The role of motivation and attitudes in adolescents' help seeking in math class. Journal of Educational Psychology, 89, p. 329-341, 1997.SÃ„LJÃ–, R. Learning and Understanding: A Study of Differences in Constructing Meaning from a Text. GÃ¶teborg: Acta Universitatis Gothoburgensis, 1982. (GÃ¶teborg Studies in Educational Sciences, n. 41)SALOMON, G. The differential investment of mental effort in learning from different sources. Educational Psychologist, 18(1), p. 42-50, 1983.SENÉCAL, C.; KOESTNER, R.; VALLERAND, R. Self-regulation: an academic procrastination. The Journal of Social Psychology, 135, 5, p. 607-619, 1995.SCHER, S.; OSTERMAN, N. Procrastination, conscientiousness, anxiety, and goals: exploring the measurement and correlates of procrastination among school-aged children. Psychology in the Schools, 39 (4), p. 385- 398, 2002.SCHOUWENBURG , H. Trait procrastination in academic settings: An overview of students who engage in task delays. In: Schouwenbu rg, H.; Lay, C.; Pylch yl, T.; Ferrari, J. (Ed.). Counselling the procrastinator in academic settings. Washington: American Psychological Association, 2004. p. 3-18.SCHUNK, D. H. The self-efficacy perspective on achievement behaviour. Educational Psychologist, 19, p. 199-218, 1984.__________. Self-efficacy and academic motivation. Educational Psychologist, 26, p. 207-231, 1991.__________. Self-regulation of self-efficacy and attributions in academic settings. In: Schun k, D. H.; Zimme rman , B. J. (Ed.). Self-regulation of learning and performance: Issues and educational applications. Hillsdale: Erlbaum, 1994. p. 75-99.__________. Goal and self-evaluative influences during children's cognitive skill learning. American Educational Research Journal, 33, p. 359-382, 1996a.__________.Teaching elementary students to self-regulated practice of Mathematical skills with modeling. In: Schun k, D. H.; Zimme rman , B. J. (Ed.). Self-regulated learning: From teaching to self-reflective practice. Hillsdale, NJ: Lawrence Erlbaum Associates, 1998. p. 137-159.__________. Social Cognitive Theory and Self-Regulated Learning. In: Zimme rman , B. J.; Schun k, D. H. (Ed.) Self-regulated learning and academic achievement: Theoretical Perspectives. 2. ed. New Jersey: Lawrence Erlbaum Associates, 2001. p. 125-151.__________. Commentary on self-regulation in school contexts. Learning and Instruction, 15, p. 173-177, 2005.TIMOTHY, J. C.; ZIMMERMAN, B. J. Self-Regulation Empowerment Program to Enhance Self-Regulated and Self-Motivated Cycles of Student Learning. Psychology in the Schools, 41 (5), p. 537-550, 2004.VANSTEENKISTE, M.; SIMONS, J.; LENS, W.; SHELDON, K. M.; DECI, E. L. Motivating learning, performance, and persistence: The synergistic effects of intrinsic goal contents and autonomy-supportive contents. Journal of Personality and Psychology, 87, p. 246-260, 2004.WINNE, P. H. Inherent details in self-regulated learning. Educational Psychology, 71, p. 3-25, 1995.__________. Experimenting to bootstrap self-regulated learning. Journal of Educational Psychology, 89 (3), p. 397-410, 1997.YOWELL, C. M.; SMYLIE, M. A. Self-regulation in democratic communities. Elementary School Journal, 99, p. 469-490, 1999.ZIESAT, H.; ROSENTHAL, T.; WHITE, G. Behavioural self-control in treating procrastination of studying. Psychological Reports, 42, p. 59-69, 1978.ZIMMERMAN, B. J. Model of self-regulated learning and academic achievement. In: __________.; Schun k, D. H. (Ed.). Self-regulated learning and academic achievement: Theory, research and practice. NY: Springer-Verlag, 1989a. p. 1-25.__________. A Social Cognitive View of Self-Regulated Academic Learning. Journal of Educational Psychology, 81 (3), p. 329-339, 1989b.__________. Dimensions of academic self-regulation: A conceptual frame-work for education. In: Schun k, D. H.; ZIMMERMAN, B. J. (Ed.). Self-regulation of learning and performance: Issues and educational applications. Hillsdale, NJ: Erlbaum, 1994. p. 3-21.__________. Developing self-fulfilling cycles of academic regulation: An analysis of exemplary instructional models. In: Schun k, D. H.; ZIMMERMAN, B. J. (Ed.). Self-regulated learning: From teaching to self-reflective Practice. NY: The Guilford Press, 1998. p. 1-19.__________. Commentary: toward a cyclicaly interactive view of self372 regulated learning. International Journal of Educational Research, 31, p. 545-551, 1999.__________. Attaining self-regulation: A social cognitive perspective. In: Boe kae rts , M.; Pint rich , P.; Zeidne r, M. (Ed.). Hanbook of selfregulation. NY: Academic Press, 2000. p. 13-39.__________. Becoming a Self-Regulated Learner: An Overview. Theory Into Practice, 41 (2), p. 64-70, 2002.__________; BONNER, S.; KOVACH, R. Developing self-regulated learners: Beyond achievement to self-efficacy. Washington, DC: American Psychological Association, 1996.__________; MARTINEZ-PONS, M. Construct validation of a strategy model of student self-regulated learning. Journal of Educational Psychology, 80, p. 284-290, 1988.__________; MARTINEZ-PONS, M. Student differences in self-regulated learning: Relating grade, sex, and giftedness to self-efficacy and strategy use. Journal of Educational Psychology, 82 (1), p. 51-59, 1990.__________; MARTINEZ-PONS, M. Perceptions of efficacy and strategy use in the self-regulation of learning. In: Schun k, D. H.; Meese , J. (Ed.). Student perceptions in classroom: causes and consequences. Hilldale, NJ: Erlbaum, 1992.__________; PAULSEN, A. S. Self-monitoring during collegiate studing: An invaluable tool for academic self-regulation. In: Pint rich , P. (Ed.). New directions in college teaching and learning: Understanding selfregulated learning. San Francisco, CA: Jossey-Bass, 1995. p. 13-27.__________; RISEMBERG , R. Research for the future. Becoming a selfregulated writer: A social cognitive perspective. Contemporary Educational Psychology, 22, p. 73-101, 1997.__________; SCHUNK, D. H. Self-regulated learning: From teaching to self-reflective practice. NY: Guilford, 1998.